Pedagogical problems of traditional and distance education.: Opportunities in the Traditional and distance learning methods, distance learningas an innovative teaching method are becoming more widespread in the modern educational space. - Djabbarov, Sherzod (Журнал иностранных языков и лингвистики, 2023)
Opportunities in the Traditional and distance learning methods, distance learningas an innovative teaching method are becoming more widespread in the modern educational space. This form of education opens up wide opportunities for students: getting education at the world's leading universities remotely, a wide range of distance learning programs, saving time and money, flexible schedule and individual study planning.